PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PERUM PERUMNAS REGIONAL V SEMARANG - Safitri, Ayu Rizka; Nugraha, Hari Susanta; Widiartanto, Widiartanto (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
Human resource management plays an active role in improving employee performance through a number of variables that influence it, including the leadership, work discipline and employee performance. Perum Perumnas Regional V Semarang is one public company engaged in the construction and housing sales nationwide. However there are still some issues regarding employee performance Perum Perumnas Regional V Semarang who have not reached the standard of performance. So this study can provide a view of the constraints experienced by employees Perum Perumnas Regional V Semarang.This research uses explanatory research type of approach by the number of respondents were 63 employees with sampling probability sampling technique. Data collection techniques in this study using a questionnaire and literature study techniques. The data obtained were analyzed quantitatively by using analytical tools such as cross table, validity, reliability, simple linear regression, multiple linear regression and hypothesis testing by t test and F test.The results showed that the presence of a significant and positive impact between employment and kepemimnan discipline on employee performance. Labor discipline became one of the dominant factors that impact on employee performance. Suggestions can be submitted is the leadership in general has shown a high condition. For the sake defend, managers need to provide a more open opportunity for every employee to argue as well as in making employment decisions. Labor discipline in general have shown a high condition. Efforts to maintain these conditions should continue to be done. In order to improve better work discipline and its application accordingly, should the company give closer scrutiny in any violations committed by employees